The Jerusalem Temple in diaspora : Jewish practice and thought during the Second Temple period - Trotter, Jonathan Robert, (Supplements to the Journal for the Study of Judaism;, 2019)
In The Jerusalem Temple in Diaspora, Jonathan Trotter shows how different diaspora Jews' perspectives on the distant city of Jerusalem and the temple took shape while living in the diaspora, an experience which often is characterized by complicated senses of alienation from and belonging to an ancestral homeland and one's current home. This book investigates not only the perspectives of the individual diaspora Jews whose writings mention the Jerusalem temple (Letter of Aristeas, Philo of Alexandria, 2 Maccabees, and 3 Maccabees) but also the customs of diaspora Jewish communities linking them to the temple, such as their financial contributions and pilgrimages there.